Andropause in Iranian Men: Related Factors and Consequences; A Systematic Review - Aliakbari, Fereshteh; Allameh, Farzad; Tavakoli, Anahita; Ajorloo, Mehrnaz; Hosseini, Mohammad Ali; Shojaeefar, Ehsan (Archives of Men's Health, 2020)
Introduction: Andropause is a syndrome with a slow progression that is associated with androgen deficiency in older men. This study aimed to collect all scientific data about the factors that cause the occurrence of andropause in Iranian men as well as the aspects of life which can be affected by this disorder. Materials and Methods: Searching was conducted in international databases including MedLine, Scopus, Web of Science, ProQuest, and national database (SID) from inception until December 2019. Retrieved studies were reviewed by two researchers independently and selected studies were summarized in a table. Results: Finally, 21 related studies were included and summarized information showed that andropause can be negatively affected by age, lower testosterone levels, smoking, lower economic status, lower educational level, and poor employment status. Some studies have also implied that there is a significant correlation between andropause and quality of life, sleep quality, depression, anxiety, marital dissatisfaction, urinary incontinence, coronary heart disease, and metabolic syndrome. Conclusion: According to the collected data in this present study, Iranian studies have covered a wide variety of complications and related factors in the field of andropause but, we still lake some studies about other aspects of andropause such as musculoskeletal impairment, erectile dysfunction, memory and cognitive disorders, skin and hair disorders, decreased libido, and other mood disorders.